The unwanted pregnancy - Stone, Sharon H. (1974)
A questionnaire was submitted to the mothers of 200 consecutively delivered infants; 15% of mothers were unmarried. The results showed a high prevalence of unwanted pregnancy, most accounted for by well educated, married women having their first or second baby, and despite access to contraceptive agents. Most of the married women and over 50% of the unmarried who had not wanted to become pregnant wanted the baby after its birth.